Spontaneous versus induced hydrogen and deuterium helical shaped plasmas with electron internal transport barriers. (30th July 2015) - Gobbin, M; Franz, P; Auriemma, F; Lorenzini, R; Marrelli, L
Abstract: Electron internal transport barriers (eITBs) in high current plasmas with helical equilibria of the reversed field pinch experiment RFX-mod are analyzed and characterized in detail thanks to a high time resolution double filter diagnostic for the electron temperature spatial profile determination. The large amount of data provided by this diagnostic has required the development of dedicated algorithms and the identification of suitable parameters, reported and described in this paper, in order to perform automatic statistical studies. These numerical tools have been used to examine the effect of three dimensional (3D) magnetic fields applied by the RFX-mod 192 active coils in deuterium and hydrogen discharges with the aim to improve the sustainment and control of helical equilibria with eITBs. It is shown that 3D fields partially increase the occurring of helical states but with only a moderate effect on the eITBs duration; moreover, they have a different impact on the confinement properties in hydrogen and deuterium discharges. Numerical simulations, by the Hamiltonian guiding center code ORBIT, investigate the effect of magnetic topology in plasmas with and without the application of 3D fields on deuterium and hydrogen test ions transport. Results from numerical studies are in agreement with estimates of the particle confinement times showing that particle transport is reduced in deuterium plasmas but not significantly affected by the application of helical boundary conditions.